KEYAKINAN DIRI (SELF EFFICACY) SISWA BERKEBUTUHAN KHUSUS DALAM MENGENYAM PENDIDIKAN DI SEKOLAH INKLUSI - Taufik Muhtarom (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
The aim of this study is (1) to determine the students self efficacies with Special Needs in inclusive schools; (2) to find out what are the factors that must be considered in improving self-confidence (Self Efficacy) in special needs students in inclusive school. This research using qualitative descriptive analysis. The data collected by techniques such as triangulation. Triangulation means of data collection techniques are combining of various data collection techniques and sources of existing data that includes observation, interviews, and documentation. While the steps of data analysis in this study include data collection, data reduction, data presentation, and conclusion. The results of this research is Self-confidence (self-efficacy) of students with special needs in SD Negeri Karanganyar quite good. Only 4 aspects of the 10 aspects of self-confidence (self-efficacy) of students with special needs that need to be improved. While the six other aspects are good. All six aspects of self-confidence of students with special needs that need to be maintained is the aspect of the perception of students with special needs will be its ability, readiness in learning, attitudes or reactions to novelty, diligent efforts in completing the task, the ability to produce work (productivity), and the ability to self-regulate. While these four aspects are still lacking is knowledge of learning, mastery of skills in certain competencies, creative ability to solve problems (inguenity), and the ability to face the threat (threat). Factors to consider in improving self-confidence (self-efficacy) students with disabilities in inclusive schools is the availability of space assessment, special assistant teacher availability, systems management class inclusion, and skills of classroom teachers to guide and direct students with special needs in an effort to optimize their potential.